Prevalence of mutans streptococci in 93 members from six Brazilian families (Pesquisa Odontológica Brasileira, 2001)
Several studies report that mutans streptococci (MS) are closely associated with caries in humans and that there is a correlation between the number of carious lesions and the levels of MS in the saliva of children and adults. The presence of MS in the saliva of 93 members of six Brazilian families with at least 3 generations was investigated. Samples of whole unstimulated saliva were collected and diluted. Aliquots of 50 mul of each suspension were dropped onto SB20 agar and incubated in a candle jar at 37°C for 72h. Colonies resembling MS were counted, collected, seeded in thioglycollate medium and subjected to biochemical typing. Mutans streptococci were isolated from 80 subjects (86.0%) and the counts ranged from 3.0 x 10² (log 2.477) to 1.6 x 10(8) (log 8.204) CFU/ml of saliva. All of the 73 adults were colonized by MS, but the bacteria were detected in only 7 (35.0%) of the 20 children evaluated. Streptococcus mutans occurred in 78 subjects (97.5%), and 51 (63.7%) were monocolonized. S. sobrinus occurred in 29 individuals (36.3%) and 2 (2.5%) were monocolonized. Twenty-seven (33.8%) subjects were multicolonized with S. mutans and S. sobrinus. This study showed a high prevalence (86.0%) of mutans streptococci in the saliva of members of the studied families, which suggests the risk of intrafamilial transmission.